Pain experience and management in a forensic intellectual disability service. Issue 2 (2014) - ,; ,
Abstract : Purpose – Research investigating the experience and management of pain in people with intellectual disabilities has mainly been carried out in community services. The purpose of this baseline audit aims to examine this area in a forensic intellectual disability setting.Design/methodology/approach – A baseline audit of pain management was carried out. Audit standards were derived from recent research, and the performance on each measured. Patients and nurses were interviewed. The audit included 82 patients, of which 64 were interviewed. Twelve nurses were interviewed. Health Action Plans and medication files were accessed for information.Findings – There were interesting differences and similarities in the experience and management of pain between community and forensic intellectual disability patients. Within this sample, most patients were able to communicate their pain, and access appropriate treatment. However, a minority required further support. Nurse decision making about providing pain treatment was affected by fears of manipulation, contributing to addition and disbelieving the patient. Additionally, a number of patients appeared to have insufficient knowledge about how to best manage pain.Practical implications – Results suggested that a standardised approach to pain management, incorporating policy, staff training, and health promotion and psycho‐education for patients, would have benefits for both patients and staff within secure intellectual disability services.Originality/value – At present, there is little research focusing on pain experience and management in forensic intellectual disability settings.